1998
DOI: 10.1007/s004210050429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing running velocity on electroencephalogram in a field test

Abstract: This study was designed to measure the electroencephalogram (EEG) after exercise with increasing intensity. In a field test with increments in running velocity a 2-min EEG was recorded, together with blood lactate concentration and heart rate, after each stage. An individual protocol was used, with up to six stages of running to ensure comparability of exercise intensity among the subjects, in each of 19 athletes (17 men, 2 women) experienced in leisure-time running. The exercise consisted initially of three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 21 publications
4
36
0
Order By: Relevance
“…however, other studies that found relevant outcomes in this band analyzed raw absolute power values 3 . Due to the lack of normality in EEG data, they should be previously treated with a log power transformation 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…however, other studies that found relevant outcomes in this band analyzed raw absolute power values 3 . Due to the lack of normality in EEG data, they should be previously treated with a log power transformation 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of quantitative electroencephalography (qEEG) are used to describe functional topographical alterations of cortical activity in fatigue states, e.g., sleep deprivation 1,2 . In this context, it has been suggested that EEG might be especially appopriate for examining the effects of physical fatigue caused by maximal exercise 3 . Changes in the brain electrical activity following exercise might be caused by different factors, such as: changes in body temperature and arousal levels by hypothalamic modulation 4,5 , alterations in cerebral blood flow 6,7 and individual emotional state 8,9 .…”
mentioning
confidence: 99%
“…This physiological condition has been described as producing beneficial adaptive changes in the cardiovascular (17)(18)(19) and nervous systems (20)(21)(22)(23) and altering the endogenous level of ET-1 (13). In experiments where vascular tissue was studied, intact aortic strips were chosen, and when nervous system was analyzed, slices of cerebral cortex (the brain area influenced by afferent systems from working muscle and emotional processes) and cerebellum (the brain area involved in the motor processes) were used.…”
Section: Discussionmentioning
confidence: 99%
“…Since aortic blood flow increases during treadmill training in the rat (16), it is conceivable that chronic exercise induces adaptive changes in the aorta, thereby contributing somehow to the modification of aortic function, as has been widely reported (17)(18)(19). In addition, there is evidence of exercise-induced changes in the nervous system (20)(21)(22)(23), and it has been suggested that in the brain these changes might be mediated, at least in part, through neuroregulatory feedback from arterial baroreceptors to the brain (24). On the other hand, cardiovascular and neurodegenerative diseases are known to be associated with cellular apoptosis (2,3) and with oxidative stress or the vulnerability to it (25).…”
mentioning
confidence: 90%
“…Both fitness in general [1][2][3][4] and acute physical activity [5,7] exert clearly detectable effects on the human EEG. Because until today these effects have been investigated only for relatively short or moderate exercise intervals that did not exceed 1 or 2 h (for a review see [8]), we addressed this question by recording EEG data during an extralong (24 h) physical exercise.…”
Section: Ntroductionmentioning
confidence: 99%